Influence of some site factors on germinative parameters of Quercus seeds - Flores, Andrés (International Journal of Forest, Animal and Fisheries Research, 2022)
The genus Quercus has a high economic and ecological potential in Mexico. Nonetheless, its populations are reducing yearly, which demands the implementation of efficient management strategies to preserve them. To determine germinating capacity of seeds, and to learn about their relationship with some conditions of collecting sites (latitude N, accumulated degree-days >5 C in the frozen-free period (AD), precipitation of growing season (PGS)) we used information of seeds and collecting sites for natural populations of Quercus crassifolia, Q. jonesii, Q. polymorpha and Q. potosina. We determined that Q. potosina, the northernmost population; showed higher values of seeds mean weight, percentage of germinated seeds (PGS), average germination time (AGT), peak value (PV), and germination energy (GE), than other species. Q. polymorpha also showed high mean values of seeds weight, PGS, PV, and GE and it was collected at northern latitudes near those of Q. crassifolia and Q. jonesii. Q. jonesii was the southernmost population and showed lower values in these parameters. On the other hand, the analysis also determined that Q. jonesii, Q. plymorpha, and Q. potosina had quicker germination than Q. crassifolia. We inferred that for the species in the analyzed sites, increasing PGS improves sites conditions, which promotes better germination of germplasm.